2019
DOI: 10.1007/s00424-019-02260-9
|View full text |Cite
|
Sign up to set email alerts
|

Altered force generation and cell-to-cell contractile imbalance in hypertrophic cardiomyopathy

Abstract: Hypertrophic cardiomyopathy (HCM) is mainly caused by mutations in sarcomeric proteins. Thirty to forty percent of identified mutations are found in the ventricular myosin heavy chain (β-MyHC). A common mechanism explaining how numerous mutations in several different proteins induce a similar HCM-phenotype is unclear. It was proposed that HCM-mutations cause hypercontractility, which for some mutations is thought to result from mutation-induced unlocking of myosin heads from a so-called super-relaxed state (SR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 138 publications
1
28
0
Order By: Relevance
“…In fact, we observed breaks and clustering of reconstituted thin filaments with the infantile RCM mutations p.cTnI-R170G/W, though this might not be typical for RCM only [ 67 ]. Moreover, the pattern of cardiomyocytes showing different amounts of mutant and wild type proteins might contribute to the dysfunction of the myocardium [ 136 , 137 ]. In different cardiomyocytes of a tissue mRNAs are formed in different amounts at random, leading to different expression levels of wild type and HCM mutant proteins.…”
Section: Molecular Mechanisms In Rcmmentioning
confidence: 99%
“…In fact, we observed breaks and clustering of reconstituted thin filaments with the infantile RCM mutations p.cTnI-R170G/W, though this might not be typical for RCM only [ 67 ]. Moreover, the pattern of cardiomyocytes showing different amounts of mutant and wild type proteins might contribute to the dysfunction of the myocardium [ 136 , 137 ]. In different cardiomyocytes of a tissue mRNAs are formed in different amounts at random, leading to different expression levels of wild type and HCM mutant proteins.…”
Section: Molecular Mechanisms In Rcmmentioning
confidence: 99%
“…The assumption that variable fractions of mutated mRNA from cell to cell correspond to a similar variability also at the protein level is strongly supported by the large functional variability among individual HCM cardiomyocytes (Kraft et al 2016 ; Montag et al 2018 ). Additional evidence for variable allele-specific protein distribution from cell to cell is provided by independent studies that showed a patchy distribution of wild-type cMyBP-C protein from cell to cell and even within individual cardiomyocytes of HCM patients with cMyBP-C truncation mutations (Aldag-Niebling et al 2018 ; Kraft and Montag 2019 ; Parbhudayal et al 2018 ; Theis et al 2009 ). The truncations lead to haploinsufficiency; thus, the remaining protein in the sarcomeres originates just from the wild-type allele.…”
Section: Translation Of Unequal Allelic Mrna Fractions From Cell To Cmentioning
confidence: 99%
“…In addition, a recent publication shows that MYBPC3 -mRNA is transported to the Z-disc where it is translated and incorporated into the sarcomeres (Lewis et al 2018 ). If the mRNA from a burst of one allele is transported to a certain area of a cell, this may lead to the observed uneven distribution of wild-type cMyBP-C within individual cardiomyocytes (Aldag-Niebling et al 2018 ; Kraft and Montag 2019 ; Theis et al 2009 ). Taken together, model calculations as well as uneven distribution of wild-type cMyBP-C and functional variability from cell to cell strongly suggest that allelic mRNA-imbalance translates into imbalance of wild-type and mutated protein from cell to cell.…”
Section: Translation Of Unequal Allelic Mrna Fractions From Cell To Cmentioning
confidence: 99%
“…Sarcomere/myofibrillar disarray is a typical feature of myopathies, mainly caused by dysfunction of the contractile proteins, resulting in altered force generation [3]. Sarcomere disarray is extensively documented in human heart disorders such as hypertrophic cardiomyopathy (HCM), which is primarily caused by point mutations in cardiac β‐myosin heavy chain, or cardiac myosin binding protein C, among other proteins [4,5]. Besides cardiomyopathies, another striking example of sarcomere disarray is cachexia – an end‐stage chronic illness in people suffering from diseases, particularly cancer [6,7].…”
Section: Introductionmentioning
confidence: 99%